Algal oil alleviates antibiotic-induced intestinal inflammation by regulating gut microbiota and repairing intestinal barrier - Zhang, Huimin; Xu, Zhenxia; Chen, Wenchao; Huang, Fenghong; Chen, Shouwen; Wang, Xu; Yang, Chen (Frontiers in Nutrition, 2023)
Taking antibiotics would interfere with gut microbiota and increase the risk of opportunistic pathogen infection and inflammation. Recent researches revealed the potential anti-inflammatory advantage of n-3 PUFA (Polyunsaturated fatty acids) for improving intestinal inflammation. Here, we assessed the anti-inflammatory effect of algal oil rich in n-3 PUFA on mucosal injury and intestinal inflammation induced by ceftriaxone sodium (CS). Male C57BL/6 mice were treated with two kinds of algal oil after CS gavage, which were obtained from Schizochytrium sp. cultures using Yeast extract (YE) and Rapeseed meal (RSM) as substrate, respectively. Both YE and RSM algal oils markedly reduced mucosal damage and intestinal inflammatory responses in CS-treated mice by inhibiting the pro-inflammatory cytokine interleukin (IL)-6 and reducing myeloperoxidase (MPO) activity. In addition, fluorescence immunohistochemistry showed that the tight junction protein ZO-1 was increased in mice supplemented with YE and RSM algal oil. Furthermore, YE algal oil promoted the beneficial intestinal bacteria such as Lachnospiraceae and S24_7 compared to the CS group, while supplementation with RSM algal oil enriched the Robinsoniella. Spearman’s correlation analysis exhibited that Melissococcus and Parabacteroides were positively correlated with IL-6 but negatively correlated with IL-10. The different modulation pattern on intestinal microbiota for these two algal oils might be related to the content of n-3 PUFA (docohesaexanoic acid (DHA), eicosapentaenoic acid (EPA)) and myristic acid(C14:0). These results suggest the potential of algal oil as a functional food to prevent antibiotic-induced metabolic and microbial disorders.